2014
DOI: 10.1155/2014/616850
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hypoxia-Inducible Factor-1α, Glucose Transporter-1, (GLUT-1) and Carbon Anhydrase IX in Endometrial Cancer Patients

Abstract: Hypoxia-inducible factor-1α (HIF-1α), glucose transporter-1 (GLUT-1), and carbon anhydrase IX (CAIX) are important molecules that allow adaptation to hypoxic environments. The aim of our study was to investigate the correlation between HIF-1α, GLUT-1, and CAIX protein level with the clinicopathological features of endometrial cancer patients. Materials and Methods. 92 endometrial cancer patients, aged 37–84, were enrolled to our study. In all patients clinical stage, histologic grade, myometrial invasion, lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 36 publications
3
46
1
Order By: Relevance
“…3). In agreement with the majority of literature data, our results were capable statically to show increased cytoplasmic and/or membranous expression of GLUT1 in ECs compared to normal endometrium [11][12][13][14][15][16][17][18][19][20][21][22]. Decreased GLUT1 expression in normal endometrium as well as its weak expression in non-cancerous lesions and overexpression in endometrial cancer suggests that this molecule might be involved in endometrial carcinogenesis as the findings of this study and others [12,14] showed significant association with tumor stage.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…3). In agreement with the majority of literature data, our results were capable statically to show increased cytoplasmic and/or membranous expression of GLUT1 in ECs compared to normal endometrium [11][12][13][14][15][16][17][18][19][20][21][22]. Decreased GLUT1 expression in normal endometrium as well as its weak expression in non-cancerous lesions and overexpression in endometrial cancer suggests that this molecule might be involved in endometrial carcinogenesis as the findings of this study and others [12,14] showed significant association with tumor stage.…”
Section: Discussionsupporting
confidence: 92%
“…In endometrial neoplasms, nevertheless, many studies [11][12][13][14][15][16][17][18][19][20][21][22] tried to find a comparable association and verify that the IHC GLUT1 phenotype could be utilized as a diagnostic and prognostic tissue marker, but the findings were inconsistent (Tab. 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glut-1 expression in lung cancer was demonstrated to be associated with its malignant stage, with more advanced stages typically being accompanied with higher expression levels of Glut-1 (28). Expression of Glut-1 in endometrial lesions has also been demonstrated to be associated with cancer differentiation, and it is possible to use Glut-1 expression to effectively distinguish the malignant tendency from a benign tissue to atypical hyperplasia of the endometrium (29). Similarly, in pancreatic ductal adenocarcinoma and laryngeal cancer, Glut-1 expression levels have been demonstrated to be positively correlated with the clinical malignant stage (30).…”
Section: Discussionmentioning
confidence: 99%
“…3 Previous studies indicated that upregulation of GLUT-1 contributed to an improved glucose metabolism, which was required in proliferating cancer cells. 2 GLUT-1 is overexpressed in many tumors, including breast, 4 colorectal, 5 endometrial, 6 and ovarian 7 carcinomas. GLUT-1 was reported originally as a marker of infantile skin hemangioma.…”
Section: Introductionmentioning
confidence: 99%